The impact of proton pump inhibitor exposure on pneumonia: an updated meta-analysis based on randomized controlled trials - Wu, Zhujun; Wu, Yixuan; Xiang, Zhiyi; Qiu, Yi; Xuan, Wangyi; Zhang, Shengying (Frontiers in Pharmacology, 2025)
BackgroundThe association between proton pump inhibitor (PPI) use and pneumonia risk remains inconclusive. This meta-analysis explores the impact of PPI use on the risk of pneumonia.MethodsWe systematically searched for relevant randomized controlled trials in PubMed, Web of Science, EMBASE and Cochrane Library from January 2000 to March 2025. Relative ratio and 95% confidence interval were calculated to quantify the association between proton pump inhibitor use and pneumonia incidence.ResultsThe analysis included 20 RCTs involving 29,100 participants. Compared to the non-PPI group, the PPI-exposed group showed a higher incidence of pneumonia in the general population (RR = 1.10, 95% CI: 0.99-1.21, p = 0.07) and for hospital-acquired pneumonia (HAP) (RR = 1.12, 95% CI: 1.00-1.26, p = 0.06), although the differences were not statistically significant. A higher incidence of pneumonia was observed in the intervention group among the Asian population (RR = 1.30, p = 0.02), particularly in Iran (RR = 2.73, p < 0.001) and among Asian users of pantoprazole (RR = 1.94, p = 0.05). No significant differences in pneumonia incidence were found between groups among participants from Europe (RR = 1.04, p = 0.67) or America (RR = 1.02, p = 0.95), for ventilator-associated pneumonia (VAP) (RR = 1.17, p = 0.11), or among participants in intensive care units (ICUs) (RR = 1.05, p = 0.29) or out of ICUs (RR = 1.28, p = 0.14).ConclusionThe use of PPI might increase the risk of pneumonia in general population, especially among Asians (in Iran and in the Asian users of pantoprazole), HAP.Systematic Review RegistrationIdentifier, CRD420251021884.